Sources and Channels of Information Used by Educational Program Clients - Glenn D. Israel; Kristen M. Wilson (Journal of Applied Communications, 2006)
Organizations that want to create change through educational programs need to engage clients in a process that makes use of existing communication networks. Most clients use a repertoire of sources and channels for becoming aware of, learning about, and making decisions about practice or technology adoption. This paper focuses on one group of clients served by Cooperative Extension - horse owners - to identify patterns in the sources and channels of information they use. Further, the association between sets of channels and sources is assessed, controlling for relevant client attributes. The results show that horse owners have four correlated sets of information sources and four sets of information channels. The net influence of channels on clients' use of sources varies, with traditional Extension channels, one-on-one consultations, and Internet channels being strongly associated with the use of sources characterized by linkages outside the community. Overall, the results suggest that horse owners can be sorted into distinct market segments that use specific sources and channels. These findings can guide the design of communication strategies for Extension professionals serving adult horse owners in Florida, as well as provide general rules for others involved in developing educational programs for other clients.